Nephroblastomas Show Low Expression of MicroR-204 and High Expression of its Target, the Oncogenic Transcription Factor MEIS1. (May 2014) - Koller, Karin; Pichler, Martin; Koch, Karin; Zandl, Martina; Stiegelbauer, Verena; Leuschner, Ivo; Hoefler, Gerald; Guertl, Barbara
By comparing several studies we identified a possible deregulation of the transcription factors PBX2 (pre–B-cell leukemia homeobox 2) and one of its binding partners, MEIS1 (Meis homeobox 1) in nephroblastomas. The regulation of MEIS1 is complex, and its expression is known to be influenced by changes of promoter methylation and binding of microRNA-204 (miR-204). Therefore, in our study, we assessed the expression of MEIS1 and PBX2 and the factors regulating expression of MEIS1 in nephroblastomas. MEIS1 and PBX2 messenger RNA (mRNA) and protein levels were investigated by quantitative real-time-polymerase chain reaction (qRT-PCR) and immunohistochemistry. Promoter methylation of MEIS1 was evaluated using a methylation-specific PCR assay. Expression levels of miR-204 were examined by qRT-PCR. Eighteen of 21 nephroblastomas showed a high level of MEIS1 mRNA, and 22 of 26 samples had a specific nuclear protein expression. MicroRNA-204 had a statistically significantly lower expression in all nephroblastomas investigated compared with renal parenchyma, but no change of MEIS1 promoter methylation status was noted. Eleven of 23 nephroblastomas had a high expression of PBX2 mRNA, and 15 of 23 samples had a specific nuclear protein expression was noted. In our study, we demonstrated an expression of MEIS1 and its binding partner PBX2 in most nephroblastomas. The statistically significantly lower expression of miR-204 in all nephroblastomas investigated might point to an involvement of miR-204 in the regulation of MEIS1 in nephroblastomas.